Variation of Fermentation Time of Crystal Guava Leaf Tea (Psidium guajava L.) on Antioxidant Activity and Sensory Profile with Rate-All-That-Apply Method: Guava Leaf Tea - Rosida Rosida; Anugerah Dany Priyanto; Hadi Munarko; Muhammad Alfid Kurnianto (Food Science and Technology Journal (Foodscitech), 2023)
A concise and factual abstract is required. The abstract should state briefly the purpose of the research, the principal results and major conclusions. An abstract is often presented separately from the article, so it must be able to stand alone. For this reason, references should be avoided, but if essential, then cite the author(s) and year(s). Also, non-standard or uncommon abbreviations should be avoided, but if essential they must be defined at their first mention in the abstract itself. The abstract should not exceed 250 words and is constructed in 1 paragraph written in English. Keywords: Author; Foodscitech Journal; article template